Epidermal growth factor receptor and integrins meet redox signaling through P66shc and Rac1. (October 2021) - Mushtaq, Umar; Bashir, Muneesa; Nabi, Sumaiya; Khanday, Firdous A.
Graphical abstract: Highlights: ROS acts as pivotal players in the crosstalk between epidermal growth factor receptor and integrins. Adaptor proteins such as p66Shc and Grb2 act as downstream targets activating Rac1 to increase ROS. Understanding the synergetic role of EGFR and integrins in ROS regulation will gives new dimensions to the study. Abstract: This review examines the concerted role of Epidermal Growth Factor Receptor (EGFR) and integrins in regulating Reactive oxygen species (ROS) production through different signaling pathways. ROS as such are not always deleterious to the cells but they also act as signaling molecules, that regulates numerous indespensible physiological fuctions of life. Many adaptor proteins, particularly Shc and Grb2, are involved in mediating the downstream signaling pathways stimulated by EGFR and integrins. Integrin-induced activation of EGFR and subsequent tyrosine phosphorylation of a class of acceptor sites on EGFR leads to alignment and tyrosine phosphorylation of Shc, PLCγ, the p85 subunit of PI-3 K, and Cbl, followed by activation of the downstream targets Erk and Akt/PKB. Functional interactions between these receptors result in the activation of Rac1 via these adaptor proteins, thereby leading to Reactive Oxygen Species. Both GF and integrin activation can produce oxidants independently, however synergistically there is increased ROS generation, suggesting a mutual cooperation between integrins and GFRs for redox signalling. The ROS produced further promotes feed-forward stimulation of redox signaling events such as MAPK activation and gene expression. This relationship has not been reviewed previously. The literature presented here can have multiple implications, ranging from looking at synergistic effects of integrin and EGFR mediated signaling mechanisms of different proteins to possible therapeutic interventions operated by these two receptors. Furthermore, such mutual redox regulation of crosstalk between EGFR and integrins not only add to the established models of pathological oxidative stress, but also can impart new avenues and opportunities for targeted antioxidant based therapeutics.